PENGARUH MODEL PEMBELAJARAN MANDIRI TIPE MASTER SISWA KELAS VIII SMP N 22 MERANGIN - Novia Anggraini (Pendidikan Matematika | STKIP YM Bangko, 2020)
This research is motivated by the low understanding of students' mathematical concepts, this is indicated by three indicators that have not been achieved by students. This type of research is an experimental study with aresearch Posttest-Only Control Designdesign. The sampling technique uses Simple Random Sampling. The population of this study were students of class VIII SMP N 22 Merangin with a sample of class VIII A as the experimental class and class VIII B as the control class. The data collection technique used in this study was a test of mathematical conceptual understanding. Data analysis techniques in testing the hypothesis using the Mann-Whitney test (U test). Based on the results of the study, the average value of the experimental class taught with thetype of self-learning model MASTER is 14.27 and the average value of the control class taught with the conventional model is 11.76. Value < or then Ha accepted and Ho was rejected. The conclusion of this research is that understanding of mathematical concepts taught using thetype of independent learning model MASTER is better than understanding mathematical concepts taught using conventional models in class VIII students of SMP N 22 Merangin.